Exploring the Anticancer Potential of Some Commonly used Tectaria Plants through Network Pharmacology and Molecular Docking - Jangid, Neha; Mall, Muskan; Sengar, Mohit; Mishra, Shivang; Bansal, Priya; Prakash, Surya; Kant, Krishan; Kumar, Abhishek (Journal of Neonatal Surgery, 2025)
Objective: To evaluate the anticancer potential of four Tectariaceae plants using a network pharmacology approach and identify key molecular mechanisms involved. Methods: Bioactive compounds were screened via SWISS ADME; targets were predicted using public databases. Overlapping cancer-related targets were analyzed using PPI networks, GO, KEGG, and molecular docking were done to evaluate the mechanism of action. Result and discussion: Out of 27 compounds, 15 met drug-likeness criteria. 348 overlapping targets were identified; IL-17 and TNF pathways emerged as key anticancer mechanisms. Several compounds showed strong binding affinity (≥ -6 kcal/mol) against targets like 6ESM, 51KV, 2ZOQ, and 1RE1, indicating promising anticancer activity. Conclusion: The study highlights Tectariaceae plants as potential anticancer agents, with multiple bioactive compounds targeting inflammation and immune-related pathways, supporting their role in future drug development.